A robust differential protection technique for single core delta-hexagonal phase-shifting transformers. (July 2019) - Soliman, Ismail A.; Abd el-Ghany, Hossam A.; Azmy, Ahmed M.
Highlights: An advanced differential protection is proposed for single core PSTs. Tap position is estimated as an input to the protection relay. The relay is restrained to avoid mal-operation during the energization of the PST. The 5th order harmonic is calculated as an indicator for the saturation of the CTs and series winding of the phase shifting transformer. The 5 th order harmonic is used as an indicator for the CTs and the PST saturation. Abstract: This paper presents an advanced technique for the differential protection of single core phase shifting transformers. The proposed technique is based on sensing electrical signals without sensing tap position. Only terminals currents are sensed by using two current transformers (CTs) per phase unlike other methods that need more CTs. Other methods use at least four transducers per phase and, in addition, sense the tap changer position, which increases the cost of the protection system. The proposed technique is based on the analysis of magnetically coupled and metallically connected circuits. The excitation winding currents are calculated to represent input currents to the differential protection relay. Tap changer position is estimated according to the phase shift between sources currents. The technique is checked for various types of shunt faults inside and outside the protection zone. The results prove the relay sensitivity and stability for internal and external faults, respectively. The effects of inrush current, series winding and CTs saturation are taken into consideration.